(untitled) (Medical Forum Monthly, 2024)
Objective: The rationale of our study is to compare the incidence in lactating and non lactational mothers and to findout the best management option for the benefit of patients suffering from the breast abscess. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Surgical Department of Peoples Medical College Hospital from September 2016 to August 2018. Materials and Methods: All the patients lactational and non lactational were admitted through Surgical OPD and emergency Depatment of PMC Hosptal Nawabshah Sindh. Detailed History, Clinical Examination and Required biochemical as well as imaging investigations were done followed by different surgical procedures. Results: Total 50 patients were included in this study. Of 50, 40 (80%) were lactating mothers and 10 (20%) were non lactating girls and women. Pus aspiration by wide bore cannula and ultrasounde guided was done in some patients. Incision drainage was done in most of patients. Culture and sensiticvity of pus showed Staphylococcus Areus the most common organism causing the breast abscesses in our study. Conclusion: Incision drainage produced the excellent results with no recurrence rate. C/S of pus detected the orgaism involvement and the required antbiotics were started and got good results in healing mechanism.